MicroRNA-149 Suppresses Inflammation in Nucleus Pulposus Cells of Intervertebral Discs by Regulating MyD88 - Qin, Chuqiang (Med Sci Monit, 2019)
BACKGROUND: Intervertebral disc degeneration (IDD) is associated with low back and neck pain, but the mechanisms underlying its pathogenesis are unclear. In this study, we explored the function of microRNA-149 (miR-149) in inflammatory response mediated by lipopolysaccharide (LPS) in nucleus pulposus (NP) cells. MATERIAL/METHODS: Quantitative real-time PCR was used to detect miRNA and mRNA levels, while Western blotting was utilized to determine protein levels. ELISA was used to examine chemokine production. The correlation between miR-149 and MyD88 was assessed by reporter assay. Apoptosis was examined by flow cytometry. RESULTS: miR-149 expression was significantly decreased after LPS exposure in NP cells. Overexpression of miR-149 reversed LPS-induced inhibition in aggrecan and collagen II expression and attenuated LPS-mediated promotion in the levels of MMP3, ADAMTS4, and inflammatory cytokines. Moreover, we found that miR-149 exerted its function by targeting MyD88 in NP cells. CONCLUSIONS: miR-149 can inhibit the inflammatory response mediated by LPS in NP cells, and might be a potential target for the treatment of IDD.